Bi-level Positive Airway Pressure (BiPAP) with Standard Exhalation Valve Does Not Improve Maximum Exercise Capacity in Patients with COPD. (1st February 2015) - Moga, Ana Maria; de Marchie, Michel; Saey, Didier; Spahija, Jadranka
Abstract Background: Although BiPAP has been used as an adjunct to exercise, little is know about its effect on exercise in COPD. We aimed to evaluate the acute effect of BiPAP delivered with a standard valve (Vision, Respironics), compared to no assist, on exercise capacity in individuals with COPD. Methods: Peak exercise workload (WLpeak), dyspnea (Borg), end-expiratory lung volume (EELV), tidal volume (VT), minute ventilation (VE), O2 uptake (VO2), and CO2 production (VCO2) were assessed in 10 COPD patients (FEV1 53 ± 22% pred) during three symptom-limited bicycle exercise tests while breathing i) without a ventilator (noPS), ii) with a pressure support (PS) of 0 cm H2O (PS0; IPAP & EPAP 4 cm H2O) and iii) PS of 10 cm H2O (PS10; IPAP 14 & EPAP 4 cm H2O) on separate days using a randomized crossover design. Results: WLpeak was significantly lower with PS10 (33 ± 16) and PS0 (30.5 ± 13) than noPS (43 ± 19) (p < 0.001). Dyspnea at peak exercise was similar with noPS, PS0 and PS10; at isoload it was lower with noPS compared to PS10 and PS0 (p < 0.01). VT and VE were highest with PS10 and lowest with noPS both at peak exercise and isoload (p < 0.001). EELV was similar at peak exercise with all three conditions. VO2 and VCO2 were greater with PS10 and PS0 than noPS (p < 0.001), both at peak exercise and isoload. Conclusion: Use of BiPAP with a standard exhalation valve during exercise increases VT and VE at the expense of augmenting VCO2 and dyspnea, which in turns reduces WLpeak in COPD patients.